Association of Mood and Anxiety Disorders and Opioid Prescription Patterns Among Postpartum Women. Issue 6 (6th April 2020) - Nidey, Nichole; Carnahan, Ryan; Carter, Knute D.; Strathearn, Lane; Bao, Wei; Greiner, Andrea; Jelliffee‐Pawlowski, Laura; Tabb, Karen M.; Ryckman, Kelli
Abstract : Background and Objectives: Postpartum women represent a large population with opioid exposure who also have an increased risk of experiencing mood and anxiety disorders. However, the effect that mood and anxiety disorders have on opioid use postpartum has received little attention in the literature. Therefore, the objective of this study was to examine the association of mood and anxiety disorders with filling opioid prescriptions within the first 3 months postpartum. Methods: A retrospective cohort study (n = 25 279) was completed using claims data for a sample of privately insured women who gave birth in the state of Iowa. The interactive effects of mood and anxiety disorders and delivery mode on filling at least one and two or more opioid prescriptions were examined in logistic regression models. Results: The presence of mood and anxiety disorders among women who delivered vaginally increased their odds of filling at least one opioid fill by nearly 50% (odds ratio [OR]: 1.48, 95% confidence interval [CI]: 1.35‐1.63) and by 20% (OR: 1.20, 95% CI: 1.00‐1.43) among women with cesarean delivery. Discussion and Conclusion: Postpartum women with mood and anxiety disorders were more likely to fill opioid prescriptions postpartum compared to women without these conditions. Scientific Significance: This study extends prior research by examining the intersection of risk of mood and anxiety disorders and opioid use postpartum. Findings from this study support the need for future research to identify the drivers of increased opioid use among postpartum women with mood and anxiety disorders. (Am J Addict 2020;29:463–470)